Role of knowledge sharing in rural women’s resilience and solidarity - Rodiah, Saleha; Rohayani, Henny Sri Mulyani; Alam, Pandu Watu; Abdullah, Siti Nurul Maryam (Universitas Padjadjaran, 2025)
Background: This study examined the role of knowledge sharing in strengthening resilience and solidarity among rural women’s groups in Cianjur Regency, Indonesia. Rural women, particularly female heads of households, face limited access to education, economic opportunities, and social recognition, challenges further exacerbated by cultural norms and ecological pressures following the 2022 earthquake. Purpose: This study aimed to analyze how knowledge sharing enhances resilience and to explore its impact on solidarity between academics and rural women. Methods: A qualitative case study was conducted with six purposively selected informants, including female heads of households, local women leaders, and academic facilitators. Data were collected through in-depth interviews, participant observation, documentation, and focus group discussions conducted over four months. Conclusion: Knowledge sharing is realized through participatory mechanisms such as peer-to-peer discussions, storytelling sessions, skills and entrepreneurship training, mentoring interactions with academics, focus group discussions, and continuous informal digital communication via WhatsApp groups. Findings indicate that knowledge sharing contributes to restoring self-confidence, encouraging engagement in productive activities, and strengthening mutual support mechanisms in coping with psychological stress and everyday challenges. Moreover, knowledge sharing fosters open communication, builds collective capacity, and expands access to information through collaboration with academics, thereby enhancing social solidarity. Implications: This study affirms that knowledge sharing integrates local practices with academic insights, strengthens economic independence through skills development and entrepreneurship, and builds networks that sustain community empowerment and resilience. Limitations include the small sample size and focus on a single site, suggesting the need for future multi-site, digitally oriented research.